Teachers’ Perceptions of Curriculum Changes in the Sumba, Timor, and Flores Regions - Sene, Mikael; Metom, Philipus Benitius (Graduate Program Magister Manajemen Pendidikan, 2024)
This research investigates teachers’ perceptions of transitioning from Curriculum 13 to the Merdeka Curriculum in Sumba, Timor, and Flores. Using a quantitative descriptive approach, 180 respondents participated, including 70 from Sumba, 90 from Timor, and 20 from Flores. Data was collected using a Likert scale questionnaire via Google Forms, a widely accepted method for measuring attitudes and perceptions. The questionnaire was validated by experts in the field. These research findings show that teachers perceive the transition as sufficient, with variations in aspects like absorption, understanding, evaluation, and role perception. Challenges include insufficient information about the Merdeka Curriculum, impacting implementation and outcomes. The study underscores the need for proactive measures to enhance teachers’ understanding and implementation while advocating for stability in curriculum changes, contributing to educational policy discourse and teacher professional development.